Dose-Response Relationship Between Long-Term Blood Pressure Variability and Cognitive Decline. Issue 10 (25th June 2021) - Li, Chenglong; Ma, Yanjun; Hua, Rong; Yang, Zhenchun; Zhong, Baoliang; Wang, Hongyu; Xie, Wuxiang
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We aimed to test whether higher long-term blood pressure variability was associated with accelerated rate of cognitive decline and evaluate potential dose-response relationship. Methods: Original survey data from the Health and Retirement Study and the English Longitudinal Study of Ageing were used. Standardized Z score of cognitive function was the main outcome measure. Visit-to-visit blood pressure SD, coefficient of variation, and variation independent of mean were used. Linear mixed model and restricted spline were applied to assess association and explore dose-response pattern. Segmented regression was used to analyze dose-response relationship and estimate turning point. Meta-analysis using random-effects model was conducted to pool results, with I 2 used to test heterogeneity. Results: A total of 12 298 dementia-free participants were included (mean age: 64.6±8.6 years). Significant association was observed between blood pressure variability and cognitive decline. Each 10% increment in coefficient of variation of systolic and diastolic blood pressure was associated with accelerated global cognitive decline of 0.026 SD/y (95% CI, 0.016–0.036, P< 0.001) and 0.022 SD/y (95% CI, 0.017–0.027, P< 0.001), respectively. Nonlinear dose-response relationship was found ( P< 0.001 for nonlinearity), with clear turning point observed ( P< 0.001 for change in slopes). Conclusions: Higher long-term blood pressure variability was associated with accelerated cognitive decline among general adults aged ≥50 years, with nonlinear dose-response relationship. Further randomized controlled trials are warranted to evaluate potential benefits of blood pressure variability-lowering strategies from a cognitive health perspective.